Electrophysiological Cross-Language Neighborhood Density Effects in Late and Early English-Welsh Bilinguals - Grossi, Giordana; Savill, Nicola; Thomas, Enlli; Thierry, Guillaume (Frontiers in Psychology, 2012)
Behavioral studies with proficient late bilinguals have revealed the existence of orthographic neighborhood density effects across languages when participants read either in their first (L1) or second (L2) language. Words with many cross-language neighbors have been found to elicit more negative event-related potentials (ERPs) than words with few cross-language neighbors (Midgley et al., 2008); the effect started earlier, and was larger, for L2 words. Here, 14 late and 14 early English-Welsh bilinguals performed a semantic categorization task on English and Welsh words presented in separate blocks. The pattern of cross-language activation was different for the two groups of bilinguals. In late bilinguals, words with high cross-language neighborhood density elicited more negative ERP amplitudes than words with low cross-language neighborhood density starting around 175 ms after word onset and lasting until 500 ms. This effect interacted with language in the 300-500 ms time window. A more complex pattern of early effects was revealed in early bilinguals and there were no effects in the N400 window. These results suggest that cross-language activation of orthographic neighbors is highly sensitive to the bilinguals’ learning experience of the two languages.